2021
DOI: 10.3390/jcm10040829
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Insulin Resistance and Metabolic Syndrome in Women with Hyperandrogenemia: A Comparison between PCOS Phenotypes and Beyond

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in premenopausal women, with a wide spectrum of possible phenotypes, symptoms and sequelae according to the current clinical definition. However, there are women who do not fulfill at least two out of the three commonly used “Rotterdam criteria” and their risk of developing type 2 diabetes or obesity later in life is not defined. Therefore, we addressed this important gap by conducting a retrospective analysis based on 750 women with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Finally, despite PCOS having multiple phenotypes, only four studies (Jedel et al, 2011;Almenning et al, 2015;Ribeiro et al, 2020;Benham et al, 2021) explicitly reported phenotypical subgroups within their analyses. Previous data suggest that the different phenotypical presentations of PCOS may respond differently to exercise stimuli hence this is an important area for further study (Borzan et al, 2021).…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, despite PCOS having multiple phenotypes, only four studies (Jedel et al, 2011;Almenning et al, 2015;Ribeiro et al, 2020;Benham et al, 2021) explicitly reported phenotypical subgroups within their analyses. Previous data suggest that the different phenotypical presentations of PCOS may respond differently to exercise stimuli hence this is an important area for further study (Borzan et al, 2021).…”
Section: Limitationsmentioning
confidence: 99%
“…The cohort of PCOS patients consisted of n = 550 individual serum samples, collected in Graz, Austria, under highest quality standards, and stored at Biobank Graz [55]. The Rotterdam criteria for PCOS diagnosis were applied according to the literature [59,60]. Blood sampling was performed in the morning after an overnight fast.…”
Section: Human Samplesmentioning
confidence: 99%
“…Polycystic ovary syndrome is an endocrine disorder defined as having 2 of the 3 following clinical symptoms: chronic menstrual irregularity (oligomenorrhea or anovulation), elevated levels of androgens (hyperandrogenism), and ovarian cysts detected by pelvic ultrasound (PCO) (2,8,11,13,22). Diagnosed women are categorized into 1 of 4 standard phenotypes: (a) complete phenotype-menstrual irregularity/hyperandrogenism/PCO; (b) ovulatory phenotype-hyperandrogenism and PCO; (c) nonhyperandrogenic phenotype-menstrual irregularity and PCO; and (d) the nonpolycystic ovary phenotype-menstrual irregularity and hyperandrogenism (7,8,14).…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…An estimated 20% of women of reproductive age have PCOS, making it one of the more common endocrine disorders (1,8,19,23,26). Despite this estimation, it may be possible that up to 70% of PCOS women are undiagnosed (30,42).…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%